Long-term safety, efficacy, and immunogenicity of adalimumab biosimilar BI 695501 and adalimumab reference product in patients with moderately-to-severely active rheumatoid arthritis: results from a phase 3b extension study (VOLTAIRE-RAext). (3rd October 2019) - Cohen, Stanley B.; Czeloth, Niklas; Lee, Eric; Klimiuk, Piotr A.; Peter, Nuala; Jayadeva, Girish
ABSTRACT: Objective : To evaluate long-term safety, efficacy, and immunogenicity of BI 695501 in patients with moderately-to-severely active rheumatoid arthritis (RA) who have completed VOLTAIRE-RA. Methods : Eligible patients for this phase 3b open-label extension study (VOLTAIRE-RAext), who had completed 48 weeks' treatment with BI 695501 (Group A), 24 weeks each of adalimumab RP then BI 695501 (Group B), or 48 weeks of adalimumab RP (Group C) in VOLTAIRE-RA, were enrolled. Results : Altogether, 430 patients received BI 695501 fortnightly for 48 weeks: Group A, n = 225; Group B, n = 103; Group C, n = 102. The proportion of patients with drug-related adverse events (AEs; overall 20.2%) was similar across Groups A, B, and C: 21.3%, 20.4%, and 17.6%, respectively. The majority of treatment-emergent AEs were non-serious and of mild/moderate intensity. Consistent with adalimumab RP's safety profile, most drug-related AEs were in the system organ class infections and infestations. BI 695501 and adalimumab RP responses at the end of VOLTAIRE-RA were sustained during VOLTAIRE-RAext and all efficacy and immunogenicity endpoints were similar across groups. Conclusion : Over 2 years, BI 695501 showed similar safety, efficacy, and immunogenicity to adalimumab RP, independent of initial treatment in VOLTAIRE-RA. No previously unknown adalimumab side effects were identified. Clinical trial registration : NCT02640612.